Change in quality of life of people with dementia recently admitted to long‐term care facilities. (17th November 2014) - Beerens, Hanneke C.; Zwakhalen, Sandra M.G.; Verbeek, Hilde; Ruwaard, Dirk; Ambergen, Antonius W.; Leino‐Kilpi, Helena; Stephan, Astrid; Zabalegui, Adelaida; Soto, Maria; Saks, Kai; Bökberg, Christina; Sutcliffe, Caroline L.; et al.
Abstract Aim To assess which factors are associated with change in quality of life of people with dementia who have recently been admitted to long‐term care facilities. Background Many people with dementia will be admitted to long‐term care facilities at some point during their disease. It is currently unknown which factors are associated with improvement and/or deterioration of quality of life immediately following admission. Design An observational and longitudinal survey. Methods Data on 343 people with dementia who have been recently admitted to long‐term care facilities across eight European countries were collected between November 2010–April 2012. Quality of life was assessed by people with dementia and their proxies using the 'Quality of Life‐Alzheimer's Disease scale'. Explanatory variables included cognitive status, comorbidities, activities of daily living, depressive symptoms and neuropsychiatric symptoms. Descriptive and multilevel regression analyses were performed. Results Better cognitive abilities at baseline were associated with a decrease in self‐reported quality of life. Greater dependency and more depressive symptoms at baseline were associated with declined proxy‐reported quality of life. Furthermore, an increased dependency and an increase of depressive symptoms between baseline and follow‐up were associated with a decreased proxy‐reported quality of life. On an individual level, three groups were identified, namely people whose quality of life: (1) decreased; (2) stayed the same; and (3) increased. Conclusion Cognitive functioning, functional rehabilitation and treatment of depressive symptoms should receive special attention. However, quality of life of people with dementia does not necessarily decrease after institutionalization.